PEMILIHAN JODOH MASYARAKAT SUKU JAWA DI DESA GUNUNG MULYA KECAMATAN GUNUNG SAHILAN KABUPATEN KAMPAR - Vinna Suchiyati; Swis Tantoro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Family (parents) is the main place in determining a choice, including determining the choice of a mate. Javanese parents in Gunung Mulya normally choose a partner for their children must to choose a partner with the same ethnic group, the Javanese. When a child will make her choice on someone who comes from another tribe, usually the family will consider the child is not good to be a partner. The formulation of the problem discussion in this study is the criteria parents about choosing their child's mate and the reason of parents want their children to marry with other Javanese. The subjects of this study were 7 people consisting of 4 parents whose children were married with different ethnic groups, 2 children who were married with different ethnic groups and 1 kayim (elder person). The technique of determining the informants used is purposive sampling. The method used is a qualitative research method. The theory used is the theory of family sociology about mate selection and marriage proposed by William J. Goode. The results of the study concluded that Javanese parents in Gunung Mulya Village indeed wanted their children to marry with other Javanese but were not forced (not arranged marriage). The reason why parents want their children to marry with other ethnic groups is because according to the views of Javanese parents that someone who comes from a Javanese tribe is usually hard-working, polite and responsible, and also to make it easier to adapt and customs. Keywords: Parents, Javanese, Soul Mate Selection